2015
DOI: 10.1182/blood-2015-03-635227
|View full text |Cite
|
Sign up to set email alerts
|

PKR inhibits the DNA damage response, and is associated with poor survival in AML and accelerated leukemia in NHD13 mice

Abstract: • Nuclear PKR activity represses DNA damage response signaling and DNA repair in primary hematopoietic cells.• Increased PKR promotes genomic instability and inferior outcomes in both AML and the NHD13 mouse model of leukemia.Increased expression of the interferon-inducible double-stranded RNA-activated protein kinase (PKR) has been reported in acute leukemia and solid tumors, but the role of PKR has been unclear. Now, our results indicate that high PKR expression in CD34 1 cells of acute myeloid leukemia (AML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Also EIF2AK2 is the only EIF2α kinase exists in both the cytoplasm and nucleolus, while other 3 kinases present only in the cytoplasm(68). Cheng X et al reported that high expression of EIF2AK2 was associated with worse prognosis in AML, and it reduced DNA damage response by inhibiting ataxiatelangiectasia mutated (ATM) activation, leading to accretion of leukemia in mice model (69). EIF2AK3 (also named as PKR-like endoplasmic reticulum kinase, PERK) is reported to promoted leukemia progress by stimulating the dissemination of leukemia cells in vivo (70).…”
Section: Discussionmentioning
confidence: 99%
“…Also EIF2AK2 is the only EIF2α kinase exists in both the cytoplasm and nucleolus, while other 3 kinases present only in the cytoplasm(68). Cheng X et al reported that high expression of EIF2AK2 was associated with worse prognosis in AML, and it reduced DNA damage response by inhibiting ataxiatelangiectasia mutated (ATM) activation, leading to accretion of leukemia in mice model (69). EIF2AK3 (also named as PKR-like endoplasmic reticulum kinase, PERK) is reported to promoted leukemia progress by stimulating the dissemination of leukemia cells in vivo (70).…”
Section: Discussionmentioning
confidence: 99%
“…PR55α/B55α also supports expression of miR-142-3p and suppresses expression of miR-191-5p, relevant miRNAs in AML ( 17 ). DNA damage response is impaired by dephosphorylation of ATM by PP2A-PR55α/B55α, which translocate to the nucleus by PKR ( 18 ). Extracellular survival signals activate SRC that suppresses the B subunit; when SRC is suppressed, PR55α/B55α is expressed, resulting in dephosphorylation of PKCα and suppression of PR61α/B56α protein expression, with concomitant induction of MYC ( 19 ).…”
Section: Protein Phosphatase 2amentioning
confidence: 99%
“…12 Although PKR is primarily found in the cytoplasm where it regulates translation, about 20% of PKR is nuclear where it has been shown to regulate RNA splicing, mRNA stability, and ribosome biogenesis and affect diseases including acute myeloid leukemia AML. 1618 …”
Section: Introductionmentioning
confidence: 99%